Histopathological characteristics and CD163 immunostaining pattern in fibrous papule of the face. (2nd December 2020) - Tokat, Fatma; Sezer, Engin; Duman, Deniz; Durmaz, Emel Öztürk; İnce, Ümit
Abstract: Background: Signs of inflammation including epidermal interface changes, spongiosis, and dermal inflammation as well as pagetoid dyskeratosis are rarely described in fibrous papule (FP). We aimed to describe the inflammatory parameters, the rate of pagetoid dyskeratosis, along with CD163 immunohistochemical staining as an adjunctive diagnostic tool in FP. Methods: Histopathology samples of all biopsy‐proven FP cases were retrieved from archives and investigated for inflammatory parameters, presence of pagetoid dyskeratosis, as well as CD163, CD10, and CD34 immunostaining pattern of dermal spindle/stellate or multinucleate cells (graded from 0 to 4). Results: Thirty‐two cases of FP were identified. A high rate of inflammatory parameters including interface changes (20/32), spongiosis (31/32), and dermal lymphocytic inflammation (31/32) were detected. Pagetoid dyskeratosis was identified in eight out of 32 cases (25%). A grade 4 staining revealing a strong dendritic pattern was confirmed in all FP cases with CD163 immunohistochemistry including atypical variants such as granular FP, compared with CD10 (11/32) and CD34 (3/32). Conclusion: The dendritic cellular proliferation in FP may represent an inflammatory response to various stimuli; pagetoid dyskeratosis is a relatively common and underrecognized epidermal feature and CD163 immunostaining may be used as an adjunctive diagnostic tool in unusual histopathological subtypes.